Canine multifocal retinopathy in the Australian Shepherd: a case report - Hoffmann, Ingo; Guziewicz, Karina E.; Zangerl, Barbara; Aguirre, Gustavo D.; Mardin, Christian Y. (Veterinary Ophthalmology, 2012)
A 1-year-old Australian Shepherd (AS) was presented for a routine hereditary eye examination. During the examination multiple raised, brown to orange lesions were noted in the fundus, which could not be attributed to a known retinal disease in this breed. As they clinically most closely resembled canine multifocal retinopathy (cmr) and no indication of an acquired condition was found, genetic tests for BEST1 gene mutations were performed. These showed the dog to be homozygous for the cmr1 (C73T/R25X) gene defect. Furthermore, ultrasound (US), electroretinography (ERG), and optical coherence tomography were performed, confirming changes typical for cmr. Subsequently, the AS pedigree members were genetically and clinically tested, demonstrating autosomal recessive inheritance with no clinical symptoms in carrier animals, as was previously described for cmr. To our knowledge, this is the first reported case of canine multifocal retinopathy in the AS breed. Further investigations are under way.
EVALuna2:21067